2010
DOI: 10.1002/biot.201000159
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐scale metabolic modeling of a clostridial co‐culture for consolidated bioprocessing

Abstract: An alternative consolidated bioprocessing approach is the use of a co-culture containing cellulolytic and solventogenic clostridia. It has been demonstrated that the rate of cellulose utilization in the co-culture of Clostridium acetobutylicum and Clostridium cellulolyticum is improved compared to the mono-culture of C. cellulolyticum, suggesting the presence of syntrophy between these two species. However, the metabolic interactions in the co-culture are not well understood. To understand the metabolic intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 53 publications
1
82
0
Order By: Relevance
“…These studies showed that co-culturing can improve H 2 production from sugars. However, there is still much to be understood about the key metabolic interactions and population dynamics in such co-cultures that are critical for improvement of syntrophic efficiency and H 2 productivity [20]. Continued improvements in our ability to track metabolite fluxes will provide a more comprehensive picture of intermediary metabolism and the factors that control the flux of organic matter that result in H 2 production.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that co-culturing can improve H 2 production from sugars. However, there is still much to be understood about the key metabolic interactions and population dynamics in such co-cultures that are critical for improvement of syntrophic efficiency and H 2 productivity [20]. Continued improvements in our ability to track metabolite fluxes will provide a more comprehensive picture of intermediary metabolism and the factors that control the flux of organic matter that result in H 2 production.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic CBM CBM that replaces the steady-state assumption with a pseudosteady-state assumption to capture changes in the system or the environment over time (49)(50)(51)(52).…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic CBMs describe bacterial growth in changing environments by relaxing the steady-state assumption of CBMs and instead assuming pseudo-steady states over short time periods (49)(50)(51)(52). CBMs have been coupled with gene expression data to probe metabolic changes in M. tuberculosis in response to hypoxia (53) or with spatial models of competing bacterial species to determine bacterial ecosystem dynamics (54).…”
mentioning
confidence: 99%
“…Modeling these communities can allow for rapid pre-screening of possible consortia, nutrient compositions, and metabolic engineering approaches to increase the efficiency and productivity of the microbial consortia [56]. Several studies modeling co-culture microbial communities using dFBA have been presented in literature [54,[57][58][59].…”
Section: Dynamic Modeling Of Microbial Communitiesmentioning
confidence: 99%